The learning curve of video-assisted thoracoscopic sleeve lobectomy in a high-volume pulmonary centerCentral MessagePerspective - Jiajun Deng, MD; Lei Jiang, MD; Shenghui Li, MD; Lei Zhang, MD; Yifan Zhong, MD; Dong Xie, MD, PhD; Chang Chen, MD, PhD (JTCVS Techniques)
Objectives: To evaluate the time course and caseload required to achieve proficiency by plotting the learning curve of video-assisted thoracoscopic sleeve lobectomy. Methods: We reviewed 127 cases of video-assisted thoracoscopic sleeve lobectomy by a single surgeon at Shanghai Pulmonary Hospital to evaluate its learning curve using the cumulative sum (CUSUM) analysis. The changes of perioperative outcomes were assessed. Results: The inflection points of the CUSUM curve were around case 30 and 90, according to which 3 phases were identified: Phase I, Phase II, and Phase III. Significant downtrends were observed regarding operative time (Phase I, 194 [173-233 minutes] vs Phase II, 172 [142-215 minutes] vs Phase III, 138 [117-164 minutes], P < .05, all), blood loss (Phase I, 200 [100-238 mL] vs Phase II, 100 [50-200 mL] vs Phase III, 50 [50-100 mL]; P < .05, all), drainage duration (Phase I [5.53 ± 1.11 days] vs Phase II [4.52 ± 1.38 days]; P < .05), and length of postoperative stays (Phase I [6.60 ± 1.13 days] vs Phase II [5.68 ± 1.47 days], P < .05). The rate of severe complications significantly decreased from Phase I to Phase II (P = .03). Conclusions: Thirty cases should be accumulated to lay the technical foundation, and 90 cases were required to achieve proficiency. The focus should now shift to providing sufficient training opportunities for centers wanting to implement this technique.